Regulation of Sugar and Storage Oil Metabolism by Phytochrome during De-etiolation. Issue 2 (20th November 2019) - Kozuka, Toshiaki; Sawada, Yuji; Imai, Hiroyuki; Kanai, Masatake; Hirai, Masami Yokota; Mano, Shoji; Uemura, Matsuo; Nishimura, Mikio; Kusaba, Makoto; Nagatani, Akira
Abstract : Phytochromes activate sugar and storage oil metabolism to support the transition from heterotrophic to photoautotrophic growth and chloroplast development during de-etiolation. Abstract: Exposure of dark-grown (etiolated) seedlings to light induces the heterotrophic-to-photoautotrophic transition (de-etiolation) processes, including the formation of photosynthetic machinery in the chloroplast and cotyledon expansion. Phytochrome is a red (R)/far-red (FR) light photoreceptor that is involved in the various aspects of de-etiolation. However, how phytochrome regulates metabolic dynamics in response to light stimulus has remained largely unknown. In this study, to elucidate the involvement of phytochrome in the metabolic response during de-etiolation, we performed widely targeted metabolomics in Arabidopsis ( Arabidopsis thaliana ) wild-type and phytochrome A and B double mutant seedlings de-etiolated under R or FR light. The results revealed that phytochrome had strong impacts on the primary and secondary metabolism during the first 24 h of de-etiolation. Among those metabolites, sugar levels decreased during de-etiolation in a phytochrome-dependent manner. At the same time, phytochrome upregulated processes requiring sugars. Triacylglycerols are stored in the oil bodies as a source of sugars in Arabidopsis seedlings. Sugars are provided from triacylglycerols through fatty acid β-oxidation and the glyoxylate cycle in glyoxysomes. We examined if and how phytochrome regulates sugar production from oil bodies. Irradiation of the etiolated seedlings with R and FR light dramatically accelerated oil body mobilization in a phytochrome-dependent manner. Glyoxylate cycle-deficient mutants not only failed to mobilize oil bodies but also failed to develop thylakoid membranes and expand cotyledon cells upon exposure to light. Hence, phytochrome plays a key role in the regulation of metabolism during de-etiolation.